1993
DOI: 10.2331/suisan.59.721
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Ultrastructure and Cytochemical Mg2+-ATPase Activity in Ordinary Muscle of Cultured and Wild Red Sea Bream during Storage in Ice.

Abstract: We made a comparative study on changes of ultrastructure and cytochemical Mg2+-adenosine triphosphatase (Mg2+-ATPase) in ordinary muscle of cultured and wild red sea bream during storage in ice.Degeneration of the Z lines of ordinary muscle was faster in cultured fish than in wild fish. In cultured fish, the structure of the Z lines became discontinuous within 1 day in ice. While, the Z lines showed continuity until day 3 in wild fish. Degenerations of other organella, such as the sarcoplasmic reticulum, mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…However, change in the property of myofibrillar protein may contribute to that in breaking strength, because degeneration of Z lines of ordinary muscle affects the tenderization of muscle during storage in ice. 16 …”
Section: Resultsmentioning
confidence: 99%
“…However, change in the property of myofibrillar protein may contribute to that in breaking strength, because degeneration of Z lines of ordinary muscle affects the tenderization of muscle during storage in ice. 16 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, degradation of myofibrillar proteins can be indirectly measured by changes in ATPase activity. This makes measure of ATPase activity useful for quality assessment of muscle (Kamal et al, 1991;Ko et al, 1991;Tachibana et al, 1993;MacDonald and Lanier, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, chub mackerel that live in the Bungo Channel are forced to exercise more intensely than those in other sea areas, and the exercise may affect the meat texture. Tachibana et al 8 . showed that ‘exercising breeding’ made the red sea bream meat tougher, and the softening phenomenon was retarded.…”
Section: Introductionmentioning
confidence: 99%